If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4h * 6h = 0 Reorder the terms for easier multiplication: 4 * 6h * h = 0 Multiply 4 * 6 24h * h = 0 Multiply h * h 24h2 = 0 Solving 24h2 = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Divide each side by '24'. h2 = 0 Simplifying h2 = 0 Take the square root of each side: h = {0}
| -2+2y=-4 | | 3-4r=10r+10 | | (3m-4n-7)-(8m+n-6)= | | 32+5n=75 | | 2y=4x-3 | | 2+11x=12x-6 | | (3m-4n-7)(8m+n-6)= | | y^2-16x-6y+25=0 | | 3(a-2)=9(a+2) | | 9x-15= | | 3=12-3x | | -7h-4=h+4 | | 62-c=42 | | -3b-2a-4c+5b-8a= | | 4d-8=19 | | 4(x-4)-11x= | | 6c-12=48 | | 25h=20h+15 | | 1-2x=16-5x | | 4y+6=-14 | | 9(6x+3)= | | 7x=11x+16 | | 3x+-7=-8 | | 9a-4a+a-10= | | 6w+5=w-35 | | 3(2t^2-5)=t | | -5x+-5=9x | | a^2x^2-8abx+16b^2=0 | | 97-4x=41x+17 | | 9=a(14) | | 11-10x=40-17x | | 10x+35=28x+35 |